Why commercial banks held excess reserves: The Japanese experience of the late '90s - Kazuo Ogawa (Osaka University, Institute of Social and Economic Research (ISER), 2004)
We investigated, empirically, why Japanese banks held excess reserves in the late 1990s. Specifically, we pin down two factors explaining the demand for excess reserves: a low short-term interest rate, or call rate, and the fragile financial health of banks. The virtually zero call rate increased the demand for excess reserves substantially, and a high bad loans ratio largely contributed to the increase in excess reserve holdings. We found that the holdings of excess reserves would fall by half if the call rate were to be raised to its level prior to the adoption of the zero-interest-rate policy, and the bad loans ratio were to fall by 50%.
Keywords: E42; E51; E52; G21; 330; Excess Reserve; Bad loans; Zero-interest-rate-policy; Zentralbank; Geldpolitik; Geldmenge; Zinspolitik; Kreditrisiko; Japan